Engineering the microbiome for animal health and conservation. Issue 6 (April 2019) - Jin Song, Se; Woodhams, Douglas C; Martino, Cameron; Allaband, Celeste; Mu, Andre; Javorschi-Miller-Montgomery, Sandrine; Suchodolski, Jan S; Knight, Rob
Interest in animal microbiomes as therapeutics is rapidly expanding, as techniques to study the microbial world decrease in cost and increase in accessibility and case studies from human medicine receive widespread attention. In this review, we summarize the current state of techniques to modify the microbiome to improve animal health, focusing on applications in domestic pets, farm animals, and in wild settings for conservation. We discuss options for modifying the microbiome, including community-wide changes such as fecal microbiota transplants, prebiotics, probiotics, and antibiotics, and more targeted approaches such as phage therapy and CRISPR-Cas. We conclude that although much remains to be done in untangling the basic biology of microbiome-directed therapies in animals, the rapid progress currently being made in human medicine and the examples to date of application of probiotics and other microbiome-directed therapies in taxa ranging from horses to salamanders to bees suggest excellent prospects for these technologies as they are further developed and as data on both the benefits and risks are carefully and systematically collected. Impact statement: Considering the clear effects of microbiota on important aspects of animal biology and development (including in humans), this topic is timely and broadly appealing, as it compels us to consider the possibilities of altering the microbiome (without antibiotics) to positively affect animal health. In this review, we highlight three general approaches to manipulating the microbiome that have demonstrated success and promise for use in animal health. We also point out knowledge gaps where further inquiry would most benefit the field. Our paper not only provides a short and digestible overview of the current state of application, but also calls for further exploration of the microbial diversity at hand to expand our toolkit, while also leveraging the diversity and flexibility of animal systems to better understand mechanisms of efficacy.